Pengarusutamaan Gender dalam Perspektif Strukturasi: Analisis Penyelenggaraan Organisasi PKK pada Pembangunan Desa - Susilowati, Retno; Khairunnas, Khairunnas; Rafinzar, Rahmat; Tamsyah, Indra (Universitas Indo Global Mandiri, 2024)
The involvement of women in several village development programs which is still very low when compared to the quantity of men's involvement in government and village development programs is the background of this research. The research was conducted in Pulau Semambu Village, Ogan Ilir. The formulation of the research problem is how the role of the PKK organization in village development is viewed from a structuring perspective. The purpose of this research is to see the role of the PKK organization in village development. The method used is Descriptive Qualitative with data analysis techniques with Miles and Huberman's interactive model and data validation with triangulation. The results showed that the role of the Pulau Semambu Village PKK organization had a positive impact on the development program, but not all of the main PKK programs had gone well. There are still obstacles in managing the PKK organization, especially human resources, infrastructure, and budget issues. The government needs to provide support to PKK managers at every level both materially and immaterially.